Bone turnover is adequately suppressed in osteoporotic patients treated with bisphosphonates in daily practice - Dijkmans Ben AC; Heijboer Annemieke C; Bultink Irene EM; Eekman Danielle A; Lems Willem F (BMC Musculoskeletal Disorders, 2011)
Abstract Background Monitoring osteoporosis therapy by measurement of bone turnover markers (BTMs) might detect non-compliance in an earlier stage of anti-osteoporosis treatment and improve persistence. Methods BTMs were measured in two groups. The first group consisted of patients newly diagnosed with osteoporosis and starting treatment. We observed which proportion of patients had a decrease of serum levels of procollagen type 1 N-terminal propeptide (P1NP) and C-terminal crosslinking telopeptide (CTX) greater than the least significant change (LSC) after 3 months of treatment. Secondly, we determined which proportion of patients who were treated with bisphosphonates for ≥ 3 months reached the biological goal of therapy, BTMs in the lower half of the normal premenopausal range. P1NP and CTX were also measured in a reference population of 34 healthy premenopausal women. Results In the first group 31 patients were included, in 25 patients (81%) levels of both markers decreased with ≥ LSC, in the other patients a possible explanation was found. In the second group 95 patients were included, in 95% the serum P1NP levels and CTX levels were in the lower half of the premenopausal range. In 6 of the 7 patients with a level above the premenopausal range a possible explanation was found. Conclusion A decrease in bone turnover ≥ LSC can be observed in the majority of newly treated patients. In chronically treated patients, 95% have a bone turnover in the premenopausal range. In most patients with inadequate suppression of BTMs during bisphosphonate treatment, an explanation was found. Monitoring treatment effect with BTMs in daily practice is feasible, and might be an additive tool in improving therapy compliance.